شبكات التواصل الاجتماعي ودورها في تطوير التعليم الجامعي: جامعة غريان نموذجًا (Comprehensive Journal of Science, 2025)
This study aimed to investigate the role of social media networks in developing university education at the University of Gharyan from the perspectives of faculty members and students, in light of the increasing use of social media in higher education. The descriptive analytical approach was adopted due to its suitability for the nature of the study, and a questionnaire was used as the main data collection tool.The study population consisted of faculty members and students at the University of Gharyan. The study sample included 50 faculty members and 100 students, with 5 student questionnaires excluded due to incomplete responses, resulting in a total of 145 valid responses for statistical analysis. The questionnaire covered several dimensions, including the reality of social media use, its contribution to improving the educational process, its impact on academic achievement and self-directed learning, as well as challenges, obstacles, and proposed solutions.The results revealed that social media networks play a positive and effective role in developing university education, particularly in enhancing communication between students and faculty members, facilitating the exchange of educational information and resources, and developing students’ self-directed learning skills. The findings also indicated an increase in students’ interaction and participation in the learning process. Facebook and WhatsApp were identified as the most commonly used social media platforms for educational purposes.However, the study also identified several challenges that limit the effective use of social media in university education, including weak internet infrastructure, lack of institutional regulations, and excessive non-academic use. Based on these findings, the study recommended the development of clear institutional policies, the provision of training programs, and the improvement of technical infrastructure to ensure effective integration of social media into university education at the University of Gharyan.